Identification of cell wall synthesis inhibitors active against Mycobacterium tuberculosis by competitive activity-based protein profiling. Issue 5 (19th May 2022) - Li, Michael; Patel, Hiren V.; Cognetta, Armand B.; Smith, Trever C.; Mallick, Ivy; Cavalier, Jean-François; Previti, Mary L.; Canaan, Stéphane; Aldridge, Bree B.; Cravatt, Benjamin F.; Seeliger, Jessica C.
Summary: The identification and validation of a small molecule's targets is a major bottleneck in the discovery process for tuberculosis antibiotics. Activity-based protein profiling (ABPP) is an efficient tool for determining a small molecule's targets within complex proteomes. However, how target inhibition relates to biological activity is often left unexplored. Here, we study the effects of 1, 2, 3-triazole ureas on Mycobacterium tuberculosis ( Mtb ). After screening ∼200 compounds, we focus on 4 compounds that form a structure-activity series. The compound with negligible activity reveals targets, the inhibition of which is functionally less relevant for Mtb growth and viability, an aspect not addressed in other ABPP studies. Biochemistry, computational docking, and morphological analysis confirms that active compounds preferentially inhibit serine hydrolases with cell wall and lipid metabolism functions and that disruption of the cell wall underlies biological activity. Our findings show that ABPP identifies the targets most likely relevant to a compound's antibacterial activity. Graphical abstract: Highlights: A serine hydrolase inhibitor library is screened against M. tuberculosis Chemoproteomic profiling shows that hit compound AA692 has multiple targets A structure-activity series helps identify targets relevant to the mode of action AA692 disrupts the cell wall, likely by inhibiting lipid and cell wall biosynthesis Abstract : Identification and validation of targets are major obstacles in discovering drugs to combat Mycobacterium tuberculosis ( Mtb ). Here, Li et al. establish a streamlined process to identify Mtb inhibitors and their targets and use a structure-activity series and activity-based protein profiling to distinguish serine hydrolases relevant to inhibitor mode of action.